Pemberdayaan Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Melalui Program Pemberian Makanan Tambahan (PMT) pada Balita Stunting di Umbulharjo, Yogyakarta - Najla Hikmalia Dhiyaa Ulhaq; Nisa Kusumawati; Salim, Agus (Jurnal Ilmu Sosial dan Humaniora, 2024)
Based on the stunting prevalence target in Yogyakarta City in 2024, namely 12%, currently there are 15 villages that have not reached the target (below 12%). Therefore, the City of Yogyakarta is accelerating the reduction of stunting through a program providing additional food or PMT which is carried out through empowering efforts to increase the income of prosperous families or UPPKS in Umbulharjo District, Yogyakarta City. This research aims to find out the process of running the program, to find out the form of UPPKS empowerment in the aspects of capital assistance and institutional strengthening and to find out what obstacles occur in the PMT program in Umbulharjo District, Yogyakarta City. This research uses descriptive qualitative methods with interviews as a form of direct observation in the field. This UPPKS empowerment can run and the results are right on target, but there are obstacles such as toddlers who are still picky about food and also the prevention of stunting from when pregnant women have not been paid attention to. This program must continue to be implemented so that the results can become a sustainable solution for handling stunting Keywords: Stunting, PMT, UPPKS, Toddlers, Umbulharjo